A Pattern Language for Social Field Shifts - Ricardo Dutra Gonçalves; Arawana Hayashi (Journal of Awareness-Based Systems Change, 2021)
The complex systemic issues of today, including climate change, racism, social inequality, mental health crisis, call for new ways of engaging the heart (feeling), mind (thinking), and will (doing) to actually change deep-rooted behaviors. To develop these new ways of engaging, one must learn how to cultivate first, one’s interior condition (the inner place from which we operate) and second, one's capacities to co-create with others the exterior conditions for healthy social relationships. In this paper, we claim that by living in a body we are embodied and that wisdom lives in a holistic knowing that includes embodied intelligence. We argue that to address the complex challenges of our times, we must cultivate embodied and perceptual capacities and a language for our embodied experience(s). Over three years of workshops with advanced practitioners of an embodied practice called Social Presencing Theater (SPT), we used embodied activities and design prompts (drawing, photo, video) to surface and make visible social patterns. This has led us to develop a language in the context of social systems change, in particular of social field shifts (i.e., transformations in the relational and felt qualities of our social systems). Through this paper we aim to contribute to social field research by proposing an embodied, visual, and verbal language for social groups to describe and reflect on social field shifts, made up of two parts: first, an aesthetic language to describe social field qualities; and second, three families of social field archetypes to describe social fields.